Review of Nanocomposites as Anti-Corrosion Coatings on Steel Military Vehicles - Adisty Sidauruk; Sovian Aritonang (International Journal of Technology and Education Research, 2026)
Corrosion is a serious problem that causes economic and environmental losses in various industrial sectors, including the military, with global costs exceeding $2.5 trillion annually. Corrosion can reduce the lifespan and performance of military equipment, increase maintenance costs, and affect operational readiness. One solution to protect metals is the use of polymer-based coatings. Nanocomposites are synthesized through a mixing process between an epoxy matrix and uniformly dispersed nanoparticles. Recent research has developed epoxy nanocomposites with nanoparticles such as TiO₂, ZnO, and SiO₂ to enhance mechanical properties and corrosion resistance. Results from several related studies show significant improvements in corrosion resistance, with certain composites such as PANi/TiO₂ and PDMASTiO₂ demonstrating good efficiency and resistance to extreme environments, which could potentially extend the lifespan of military equipment and reduce maintenance costs.